Penerapan E-Money di Sekolah Dasar sebagai Pendukung Budaya Sehat - Nugrahani, Winda Fenny; Cahyani, Oktarina; Wibowo, Dimas Satrio; Finesca, Febticia Sholekhah Putri; Putra, Renaldi Akbar Rahmadhika (Elementary Education Journal, 2022)
Background: This study aims to determine the use of emoney as a transaction tool at school to avoid buying snacks outside of school, implementing healthy canteens and eating together as a form of support for healthy canteen culture at SD Muhammadiyah 1 Ketelan Surakarta. Method: The resource persons in this study were to collect information from the principal, vice principal, canteen staff and tutors to obtain data about a healthy culture in schools. The data technique was analyzed by means of interactive analysis. Checking the validity of the data using source, technique and time triangulation. Result: This research shows that the administration process at school has used e-money both in the canteen and at BUMS because of the concerns of students' parents about students who are still buying snacks outside of school. A healthy canteen, namely the school's desire to meet the healthy needs of students is supported by eating together to support students' nutritional needs. Implication: The implications of this study are: First, the healthy food knowledge and insight related to healthy canteen. Second, the government, supported by researchers, has to design an excellent assessment system to solve time limitations. Novelty: The present study revealed the implementation of healthy culture school comprehensively.